2021
DOI: 10.1111/jdi.13555
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle changes and their impact on glycemic control and weight control in patients with diabetes during the coronavirus disease 2019 pandemic in Japan

Abstract: Aims/Introduction: This study aimed to reveal lifestyle changes and their impact on glycemic control and weight control in patients with diabetes during the coronavirus disease 2019 (COVID-19) pandemic in Japan. Materials and Methods: We retrospectively analyzed 1,402 outpatients with diabetes at a clinic in Osaka, Japan, who responded to an interview sheet regarding lifestyle changes during the COVID-19 pandemic between 28 March and 30 May 2020. The association of lifestyle changes with hemoglobin A1c (HbA1c)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 11 publications
5
40
2
Order By: Relevance
“…These differences in results may be due in part to the fact that the amount of food eaten and the amount of exercise during the lockdown varied among the target patients. As expected, an increased overall dietary intake and increased consumption of snacks were associated with worse HbA1c values, although the results varied slightly between studies ( 28 , 29 ). It was also found that, as expected, the amount of physical activity was associated with glycemic control during the COVID-19 pandemic ( 7 , 29 ).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…These differences in results may be due in part to the fact that the amount of food eaten and the amount of exercise during the lockdown varied among the target patients. As expected, an increased overall dietary intake and increased consumption of snacks were associated with worse HbA1c values, although the results varied slightly between studies ( 28 , 29 ). It was also found that, as expected, the amount of physical activity was associated with glycemic control during the COVID-19 pandemic ( 7 , 29 ).…”
Section: Discussionsupporting
confidence: 53%
“…As expected, an increased overall dietary intake and increased consumption of snacks were associated with worse HbA1c values, although the results varied slightly between studies (28,29). It was also found that, as expected, the amount of physical activity was associated with glycemic control during the COVID-19 pandemic (7,29). Indeed, in our study, there was no notable worsening of the HbA1c value in patients who responded in the questionnaire that they had eaten less or exercised more during the state of emergency (Table 2).…”
Section: Discussionmentioning
confidence: 56%
“…Other lockdown strategies involved declaration of states of emergencies by governments and reduced outings by individuals and person to person contacts, while persons were requested to avoid settings with poor ventilation [11]. There were also cancellations, postponement and scaling down of large-scale events, and closure of primary, secondary and tertiary institutions [12].…”
Section: Description Of Covid-19 and Its Lockdownmentioning
confidence: 99%
“…It is well established that the management of blood glucose and other metabolic parameters are quite challenging for patients with diabetes and this can be exacerbated by changes in lifestyle and daily routines, such as diet, exercise, insulin adjustments, emotions, stress, social relations and working activities [13]. Changes in lifestyle, such as lack of physical activities and increased intake of diet may promote weight gain, which has implications for insulin sensitivity and glycaemic control [12].…”
Section: How Covid-19 and Its Lockdown May Affect Patients With Diabetesmentioning
confidence: 99%
“…For patients with diabetes, dietary habits, activities of daily living, and mental health are particularly important in disease management, and any disruptive change is likely to adversely affect patients' glycemic and body weight control (5,6). Indeed, recent studies have evaluated the impact of the COVID-19 pandemic on the changes in lifestyles and/ or mental health and their impact on glycemic and body weight control (7)(8)(9)(10)(11)(12)(13)(14). However, these reports evaluated the early phase, approximately two months after the beginning of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%